Accelerating Financial Inclusion through Non-cash Assistance: Exploring Factor Affecting Beneficiaries Perception - Djamaluddin, Sartika (Economics and Finance in Indonesia, 2016)
Distribution of social assistance through a non-cash system is a new government breakthrough to increase transfer effectiveness and promote financial inclusion. After the pilot project in 2014, the recent study found that there is a number of beneficiaries who feel the non-cash system is difficult. Therefore they use non-cash facilities to get the transfer only and do not want to use for other financial services. This fact could become an obstacle to financial inclusion. This study aims to investigate what factors influence beneficiaries perception to use non-cash system. We conducted a survey of 139 non-cash beneficiaries in Kabupaten Cirebon, West Java and Kabupaten Pasuruan, East Java. The results showed that accessibility such as queue time, travel time and transportation cost had a significant effect on perception of non-cash system. Perceptions also vary according to beneficiary characteristics.